Prospective follow‐up of 2, 065 young unscreened women to study human papillomavirus incidence and clearance. Issue 1 (7th March 2013) - Schmeink, C.E.; Massuger, L.F.A.G.; Lenselink, C.H.; Quint, W.G.V.; Witte, B.I.; Berkhof, J.; Melchers, W.J.G.; Bekkers, R.L.M.
<x xml:space="preserve">Abstract</x> Human papillomavirus (HPV) is a necessary factor in the development of cervical intraepithelial neoplasia and cervical cancer. However, HPV is also a very common sexually transmitted virus and many women clear their infection. To study HPV incidence and clearance, 2, 065 women, aged 18–29 years, were followed for 12 months and were asked to provide a self‐collected cervico‐vaginal sample and fill‐out a questionnaire every 3 months. For HPV DNA detection, the SPF10‐DEIA LiPA25 system was used. Incidence rates of any‐type high‐risk HPV and low‐risk HPV were 17.0 per 1, 000‐person months, and 14.3 per 1, 000‐person months, respectively. HPV types 16, 52, 51 and 31 had the highest type‐specific incidence rates. HPV incidence was increased in singles, and women having a new relationship. A higher number of lifetime sex partners, and a higher frequency of sexual contacts in the past 3 months was associated with an increased HPV incidence. The overall clearance of the newly detected type‐specific high‐risk HPV infections and low‐risk HPV infections was 61.2% and 69.0%, respectively. Having a sexual relationship compared to being single, and a higher sexual age both positively influenced the clearance of any‐type high‐risk HPV. Among the women infected with HPV 16, the women who had a co‐infection had a lower proportion of clearance of HPV 16. In conclusion, in this young Dutch study population, HPV incidence rates are not related to age and comparable to other western countries. Clearance was only independently related to factors associated with sexual behavior, either past or current.